2021
DOI: 10.3390/jcm10184033
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Pulmonary Ligament Division May Be Unnecessary during Left Upper Lobectomy: Effects on Lung Volume, Bronchial Angle and Bronchial Tortuosity

Abstract: The benefits of dissecting inferior pulmonary ligament (IPL) during upper lobectomy using video-assisted thoracoscopic surgery (VATS) for early-stage lung cancer remains controversial. This study evaluates the effect of IPL dissection by comparing the lung volume, bronchial angle, and bronchial tortuosity of the left lower lobe (LLL) during VATS upper lobectomy. Medical records of all patients who underwent VATS left upper lobectomy for early-stage lung cancer were evaluated. Patients were divided into group P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
3
2
Order By: Relevance
“…Pulmonary volumetry enables objective and accurate observation of postoperative lung re-expansion. Moon et al [ 17 ] demonstrated that Group D experienced greater postoperative lung volume loss after LUL compared to Group P. In contrast, our study did not find a significant difference in pre- and postoperative lung volume change between Group P and Group D for both the left and right sides. It is conceivable that mild residual bronchial distortion may not exert a substantial influence on the recovery of lung volume, as the recovery process is subject to numerous contributing factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Pulmonary volumetry enables objective and accurate observation of postoperative lung re-expansion. Moon et al [ 17 ] demonstrated that Group D experienced greater postoperative lung volume loss after LUL compared to Group P. In contrast, our study did not find a significant difference in pre- and postoperative lung volume change between Group P and Group D for both the left and right sides. It is conceivable that mild residual bronchial distortion may not exert a substantial influence on the recovery of lung volume, as the recovery process is subject to numerous contributing factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Pulmonary volumetry is a non-invasive, easy, and fast measurement technique that uses 3D reconstruction software to analyze patient CT scans and calculate each patient's lung volume, enabling objective and accurate observation of postoperative lung re-expansion. Moon et al [17] showed that Group D had a higher postoperative lung volume loss after left upper lobectomy compared to Group P. In contrast, our study did not nd a signi cant difference in pre-and post-operative lung volume change between Group P and Group D for both the left and right side. It is possible that a mild residual bronchial distortion may not signi cantly impact the recovery of lung volume, as the recovery process is in uenced by numerous factors.…”
Section: Discussioncontrasting
confidence: 96%
“…Moon et al [ 6 ] retrospectively reviewed 80 patients who underwent VATS left upper lobectomy for early-stage lung cancer in the National Health Insurance Service database and 2 institutions in which a single surgeon was appointed to perform the surgery in each institution. There was no significant difference in the chest tube duration, change in left bronchial axial or vertical angulation.…”
Section: Resultsmentioning
confidence: 99%